2003
DOI: 10.1007/s00210-003-0740-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of the renin-angiotensin system in the compensation of quinpirole-induced blood pressure decrease

Abstract: The dopamine D(2)-like receptor agonist quinpirole has been reported to lower blood pressure. This effect appears to be mediated via activation of presynaptic D(2)-like receptors inhibiting the stimulated neural norepinephrine release. The aim of the present study was to investigate the role of renal nerves and the renin-angiotensin system (RAS) in the blood pressure lowering effect of quinpirole. Therefore, clearance experiments using different doses of quinpirole (0.3 to 100 microg/kg/min) were performed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…It must be highlighted that the selective agonists SKF-38393 (D 1 -like) or quinpirole (D 2 -like) did not affect the increase in diastolic blood pressure during the infusion of methoxamine in our experiments (not shown). In contrast, other studies have shown that activation of these receptors results in a dose-dependent decrease in diastolic blood pressure [20,21]. This apparent discrepancy could be due to the fact that i.v.…”
Section: Discussionmentioning
confidence: 82%
“…It must be highlighted that the selective agonists SKF-38393 (D 1 -like) or quinpirole (D 2 -like) did not affect the increase in diastolic blood pressure during the infusion of methoxamine in our experiments (not shown). In contrast, other studies have shown that activation of these receptors results in a dose-dependent decrease in diastolic blood pressure [20,21]. This apparent discrepancy could be due to the fact that i.v.…”
Section: Discussionmentioning
confidence: 82%
“…Blockade of AT 1 R normalizes the impaired renal vasodilator effect of D 1 -like receptor stimulation in the SHR (134). The increased vasodilatory effect of a D 3 R/D 4 R agonist (quinpirole) (203, 548) after renal denervation may also depend on a decreased activity of the renin-angiotensin system (379). …”
Section: Dopamine Receptor Interactionsmentioning
confidence: 99%
“…Mice lacking the D3 receptor are reported to be hypertensive and display abnormal regulation of the renin–angiotensin system 6 . However, in the rat, the effects of the D3 receptor subtype on the renin–angiotensin system and renal haemodynamics are still in question 7 . The D4 receptors are reported to be present in rat 8 and human atria 9 and have no effect on cardiac contractility 10 .…”
Section: Introductionmentioning
confidence: 99%